Influência de Fatores Antinutricionais da Leucena (Leucaena leucocephala e Leucaena cunningan) e do Feijão Guandu (Cajanus cajan) Sobre o Epitélio Intestinal e o Desempenho de Frangos de Corte - De Oliveira, Paulo Batista; Murakami, Alice Eiko; Garcia, Elis Regina De Moraes; Macari, Marcos [UNESP]; Scapinello, Cláudio (My University, 2000)
A trial was conducted to evaluate the influence of antinutritional factors in some feedstuffs on broiler chick's performance and intestinal epithelium. A total of 480 one-day old broiler chicks were allotted to a completely randomized experimental design with four treatments (A= corn and soybean meal based control diet; B = diet containing Leucaena leucocephala - 6% [LL]; C = diet containing Leucaena cunningan - 6% [LC] and D = diet containing Pigeous bean - Cajanus cajan - 20% [CC]), four replicates and 30 broiler chicks per experimental unit. The broiler chicks, which were fed with LL and LC containing diets showed lower weight gain and a worse feed: gain in the periods from 1 to 21 and from 1 to 42 days of age. At 21stdays of age only the broiler chicks fed with LC containing diet showed a higher villi size in jejunum and villi: crypt ratio in jejunum and ileum. There was significant increase on the number of Goblet cells in the duodenum and jejunum in the broiler chicks of all treatments at the 21st day of age, and only broiler chicks fed with LL and LC containing diets showed an increased number of Goblet cells in the ileum. At 42th day of age, an increase of Goblet cells was observed in the duodenum of broiler chicks fed with CC containing diets, and in the ileum of broiler chicks fed with LL, LC e CC containing diets. Feed intake and crypt depth were not influenced by treatments in any of the experimental periods. Alterations on jejunum villi morphology, villi: crypt ratio and increased number of Goblet cells in the initial period resulted on a worse weight gain and feed: gain in the initial and total growth periods of the broiler chicks.
Influence of Antinutritional Factors of Leucaena (Leucaena leucocephala and Leucaena cunningan) and Pigeous Bean (Cajanus cajan) on the Intestinal Epithelium and Performance of Broiler Chickens
Keywords: Antinutritional factors; Broilers chicks; Cajanus cajan; Intestinal epithelium; Leucaena cunningan and leucocephala